The evaluation of occlusal relationship between the primary canines and primary molars in 3 to 5-year-old Iranian children - Rasul Sahebalam; Sara Hajian; Tayebe Mokarami (Mashhad University of Medical Sciences, 2017)
Aim: As to the assessment of occlusal status pertaining to primary canines and molars, the latter is less within reach as it is difficult to guide jaws towards a centric occlusion while maintaining a vintage point in both direct and indirect observation.  This study was originally intended to assess primary canine occlusion as a practical indicator in the evaluation of primary molar occlusion, which is otherwise less feasible in dental examination. Method and materials: A total of 281 healthy children (145 males and 136 females), with complete primary dentition and without erupted permanent teeth and serious caries were examined by a trained student of dentistry. Occlusal patterns of primary second molars were noted as flush terminal plane, distal step and mesial step and for primary canine as class I, class II and class III with regard to Angle's classification. Results: Overall, Class II canine occlusion seemed to have coincided with more than half of the flush terminal molar occlusions (62%), whereas class I was largely associated with mesial step molars (61.2%). This was also found to be applied to cases undergoing unilateral assessment. (p